2012
DOI: 10.1371/journal.pone.0048282
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of C. elegans Longevity Genes by Human and Worm Longevity Networks

Abstract: Intricate and interconnected pathways modulate longevity, but screens to identify the components of these pathways have not been saturating. Because biological processes are often executed by protein complexes and fine-tuned by regulatory factors, the first-order protein-protein interactors of known longevity genes are likely to participate in the regulation of longevity. Data-rich maps of protein interactions have been established for many cardinal organisms such as yeast, worms, and humans. We propose that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 51 publications
1
38
0
Order By: Relevance
“…This worm longevity network was successfully used to predict new longevity regulators, and we have shown that the first‐order interactors of known worm LAGs are also likely to participate in the regulation of lifespan (Tacutu et al ., 2012). As such, it is interesting to know how many more non‐LAG targets belong to the worm longevity network (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This worm longevity network was successfully used to predict new longevity regulators, and we have shown that the first‐order interactors of known worm LAGs are also likely to participate in the regulation of lifespan (Tacutu et al ., 2012). As such, it is interesting to know how many more non‐LAG targets belong to the worm longevity network (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Gene dosage may have played a role too, for example, some genes previously reported to influence lifespan [e.g., Cdk5 in flies (Connell‐Crowley et al., 2007) and Clock (ortholog of Clk ) in mice (Dubrovsky, Samsa & Kondratov, 2010)] did not show the same effect upon shRNA knockdown. The longevity effects we observed for Gdi and rab5 were consistent in both genders and agree with the prior findings in worms (Samuelson, Carr & Ruvkun, 2007; Tacutu et al., 2012). Also, tkv and PH4alphaEFB emerged as two candidates for lifespan extension in female flies (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Tacutu et al . (2012) found that knockdown of 27% of C. elegans orthologs of genes found in human or worm longevity protein–protein interaction networks increased lifespan. While differences in strain, environment, and criteria for identifying long‐lived candidates make comparison between screens necessarily qualitative, it is remarkable that preselection of C. elegans orthologs of human genes differentially expressed with age resulted in a similar enrichment for longevity determinants as preselection based on secondary phenotypes known to correlate with C. elegans longevity.…”
Section: Discussionmentioning
confidence: 99%